Nanometer super-uniform titanium dioxide DGT binding film capable of efficiently adsorbing As and preparation method of nanometer super-uniform titanium dioxide DGT binding film

By using strain XZ-1 for biosynthesis, nano-ultrauniform Bio-TiO2-DGT binding membrane was prepared, which solved the problem of complex and poor uniformity of the existing binding membrane preparation process, achieved efficient arsenic adsorption effect, and was suitable for high-resolution imaging analysis.

CN119680520APending Publication Date: 2025-03-25AGRO ENVIRONMENTAL PROTECTION INST OF MIN OF AGRI

Patent Information

Application Number
CN202411702150.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-09-09
Filing Date
2024-11-26
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing DGT binding membrane has shortcomings in the complex preparation process, poor uniformity and large particle size, which limits its application potential in high-precision analysis and the difficulty of technology promotion.

Method used

Strain XZ-1 was used for biosynthesis, and metatitanate was used as raw material to achieve in-situ precipitation of TiO2 on the diffusion membrane, and a nano-ultrauniform Bio-TiO2-DGT binding membrane was prepared.

Benefits of technology

The prepared bonding film has the advantages of low production cost, simple operation, large adsorption capacity, high uniformity and small particle size. It is suitable for two-dimensional high-resolution imaging analysis, significantly optimizing the performance of the bonding film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119680520A_ABST
    Figure CN119680520A_ABST
Patent Text Reader

Abstract

The invention relates to a nano super-uniform titanium dioxide DGT binding film capable of efficiently adsorbing As and a preparation method thereof. Adsorption materials of As (III) and As (V), DGT devices and preparation methods thereof are covered. The material comprises a biosynthetic titanium dioxide modified binding membrane material Bio-TiO2-DGT, a diffusion membrane, a nitrocellulose membrane and the like. According to the method, metatitanic acid is taken as a raw material, biosynthesis is carried out by utilizing a strain XZ-1, and the Bio-TiO2-DGT binding membrane is prepared by in-situ precipitation of titanium dioxide. The preparation method disclosed by the invention is simple and easy to implement, and the obtained binding membrane material has the characteristics of good uniformity, nano-scale particle size of binding membrane particles, good adsorption performance on As (III) and As (V) and the like, and provides a technical support for two-dimensional high-resolution analysis of As. Meanwhile, the binding membrane not only overcomes the defects that a traditional TiO2 modified binding membrane is large in particle size, uneven, low in As adsorption capacity and the like, but also combines the advantages of biosynthesis and chemical precipitation, and has unique performance and potential application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of thin film gradient diffusion, and relates to a nano ultra-uniform titanium dioxide DGT combined membrane with high efficiency in adsorbing As and a preparation method thereof, in particular to a method for determining As(III) and As(V) using a biosynthesized titanium dioxide modified combined membrane material Bio-TiO2-DGT. Background Art

[0002] Arsenic (As) is a widely occurring metalloid element in nature that is highly toxic and can be released into the environment through natural processes and human activities. Long-term exposure to high As environments poses a serious threat to ecosystems and human health. As has diverse chemical forms, including inorganic arsenic and organic arsenic, which can exist in different oxidation states, such as -3, 0, +3, and +5. In soil, pentavalent arsenate (As(V)) and trivalent arsenite (As(III)) are the main forms of As, of which As(III) is generally considered to be more toxic than As(V). Given the potential hazards of As to the environment and health, it is particularly important to develop a tool that can achieve in situ dynamic monitoring of arsenic content in soil.

[0003] Diffusive gradients in thin-films technique (DGT), based on Fick's first law of diffusion, is an innovative in situ dynamic monitoring method specifically designed to assess the available concentrations of target pollutants (including nutrients, heavy metals, metalloids, and radioactive elements) in nature. A DGT device consists of an outer protective membrane that isolates external physical and chemical interferences; a central diffusion membrane that allows target molecules to diffuse through at a specific rate according to Fick's law; an inner binding membrane that captures and stabilizes incoming target molecules; and a device housing that supports and secures these membranes. The advantage of DGT technology lies in its ability to directly reflect the bioavailable concentration of target pollutants in environmental media—that is, the fraction with potential impact on organisms—rather than the total concentration. This feature makes DGT invaluable in assessing the ecological risk of pollutants and developing appropriate management strategies. Furthermore, DGT technology has demonstrated broad applicability and has been successfully applied to monitor a variety of environmental media, including water, soil, and sediment, providing strong technical support for environmental science research and conservation practices.

[0004] The application of DGT technology in two-dimensional high-resolution imaging analysis has become a current research feature. The technical method is to deploy a slender strip or flat DGT device in the environmental medium or directly on the microscopic interface, and recover it after exposure for a preset period of time. Subsequently, a series of high-precision analytical methods, such as two-dimensional slicing-colorimetry, laser ablation-inductively coupled plasma mass spectrometry (LA-ICP-MS) and computer / colorimetric density imaging (CID) are used to analyze the spatial distribution of target analytes enriched on the binding membrane. However, this technology is limited by the DGT binding membrane, that is, the binding membrane needs to meet the requirements of uniform distribution of adsorbent particles and a sufficiently small particle size (≤10μm). The shortcomings of the existing technology are reflected in the complex preparation process of traditional DGT binding membranes, and the prepared membrane materials often have poor uniformity and large particle size. These defects not only limit its application potential in high-precision analysis, but also increase the difficulty of technology promotion and application. The preparation method of traditional DGT-bound membranes is usually limited to directly dispersing the adsorption material in the gel matrix for solidification, or using in situ precipitation technology of the adsorption material on the surface of the diffusion gel, resulting in uneven particle size distribution. Summary of the Invention

[0005] The purpose of the present invention is to overcome the shortcomings of the existing technology and provide a nano-ultra-uniform titanium dioxide DGT-bound membrane with high-efficiency arsenic adsorption and a preparation method. The prepared membrane is more suitable for two-dimensional high-resolution imaging analysis of arsenic. Compared with several commonly used DGT-bound membranes for measuring arsenic, the membrane has the advantages of low preparation cost, simple operation, large adsorption capacity, high uniformity and small particle size. It has broad development potential and application prospects in practical application fields such as arsenic pollution monitoring, environmental risk assessment and soil / water remediation.

[0006] The present invention solves the technical problem by adopting the following technical solutions:

[0007] A nano-ultra-uniform titanium dioxide DGT combined membrane with high As adsorption efficiency is obtained by using strain XZ-1 to synthesize TiO2 and in-situ precipitate it on the diffusion membrane to obtain a Bio-TiO2-DGT combined membrane with uniform particle size.

[0008] Moreover, the strain XZ-1, the strain name is: XZ-1, the classification name is: Pantoea sp., the preservation number is: CGMCC No.32330, the preservation date is: October 24, 2024, the preservation unit is: General Microbiology Center of China Culture Collection Administration, and the preservation address is: Institute of Microbiology, Chinese Academy of Sciences, No. 3, No. 1 Beichen West Road, Chaoyang District, Beijing.

[0009] A method for preparing a nano-ultra-uniform titanium dioxide (DGT)-bound membrane capable of efficiently adsorbing As comprises the following steps: using titanic acid as a raw material, carrying out a biosynthesis process with the aid of strain XZ-1; during this process, immersing a pre-prepared diffusion membrane so that it is fully in contact with the reaction system; and promoting the conversion of TiO(OH)2 through the biological action of strain XZ-1, achieving in-situ precipitation of TiO2, thereby preparing a Bio-TiO2-DGT-bound membrane.

[0010] Moreover, the preparation method of the diffusion membrane includes the following steps: ultrasonically mixing a gel solution, ammonium persulfate, and N,N,N`,N`-tetramethylethylenediamine, pumping the mixture between two glass plates separated by a 0.04-0.08 cm thick gasket via a peristaltic pump, and curing the mixture under sealing to obtain a diffusion membrane.

[0011] Moreover, the volume ratio of the gel solution, ammonium persulfate and N,N,N',N'-tetramethylethylenediamine is 400:1-5:2-10.

[0012] Moreover, the gel solution is obtained by mixing acrylamide and allyl-modified low-temperature active agarose.

[0013] Moreover, the preparation method of the nano-ultra-uniform titanium dioxide DGT combined membrane with high efficiency in As adsorption specifically comprises the following steps:

[0014] S1, biosynthesis: the concentration of 0.5×10 9 Mix the bacterial suspension (CFU / mL) and 1-5 diffusion membranes with 0.5-1 mol / L TiO(OH)2 solution in a constant temperature shaker at 20-30°C for 2-5 hours;

[0015] S2. Chemical precipitation: After mixing, rinse with deionized water 1-2 times to wash away the bacteria, then immerse in 100 mL of 0.05 mol / L 2-(N-morpholine)ethanesulfonic acid buffer, which has been pre-adjusted to pH 6.7 with 1 mol / L NaOH solution, and soak until a white precipitate appears;

[0016] S3, water change and storage: After 20-60 minutes of gentle shaking to allow the gel to fully develop, the gel was removed from the buffer and soaked in MQ water for 24 hours, during which time the water was changed 5-6 times, and then -1 Soak in NaNO3 to obtain the Bio-TiO2-DGT combined membrane, and store it in a 4℃ refrigerator for later use.

[0017] Application of a nano-ultra-uniform titanium dioxide DGT-bound membrane with high efficiency in As adsorption in two-dimensional high-resolution imaging analysis of As.

[0018] Furthermore, a method for preparing a DGT-bound membrane suitable for two-dimensional high-resolution imaging analysis of As comprises the following steps:

[0019] (1) Preparation of bacterial suspension: 100 μL of the activated strain XZ-1 was incubated in 50 mL of LB medium at 30°C for 8 days on a shaking platform. The LB medium was prepared by dissolving 1 g of tryptophan, 0.5 g of yeast extract, and 1 g of NaCl in 100 mL of deionized water, and adjusting the pH of the medium to 7.0 with 1 mol / L NaOH.

[0020] (2) Preparation of TiO(OH)2 solution: 4.89 g of TiO(OH)2 powder was dissolved in 500 mL of deionized water and stirred at 60°C in a magnetic stirrer for 1 h.

[0021] (3) Preparation of Bio-TiO2-DGT combined membrane: 10 mL of bacterial suspension and diffusion membrane were mixed with TiO(OH)2 solution and placed on a constant temperature shaker at 30°C for 3 h. After mixing, the membrane was rinsed 1-2 times with deionized water to wash away the bacteria, and then immersed in 100 mL of 0.05 mol L -1 The buffer solution was pre-adjusted to pH 6.7 with 4 mL of 1 mol / L NaOH solution and soaked until a white precipitate appeared. After 40-60 minutes of gentle shaking to allow the gel to fully develop, the gel was removed from the buffer and soaked in deionized water for 24 hours, during which the water was changed 5-6 times, and then in 0.01 mol·L -1 Soak in NaNO3 and store in a 4℃ refrigerator for later use.

[0022] Furthermore, the XZ-1 bacterial suspension was obtained by culturing the bacterial cells in LB medium at 30° C. on a thermostat shaker at 180 rpm to the late exponential phase for 8 hours.

[0023] The advantages and positive effects of the present invention are:

[0024] The binding membrane preparation method described herein is highly simple and easy to use. The resulting binding membrane achieves significant improvements in uniformity and particle size, fully meeting the requirements of two-dimensional, high-resolution analysis. The binding membrane described herein is based on a diffusion membrane, featuring a simple production process, highly uniform materials, and fine particle size, making it ideally suited for two-dimensional, high-resolution analysis.

[0025] 2. The binding membrane of the present invention combines the dual advantages of biosynthesis technology and chemical precipitation. The binding membrane design of the present invention incorporates the high uniformity advantage of chemical precipitation, ensuring uniformity of the membrane structure and accurate analytical performance. More importantly, the binding membrane also deeply integrates the core advantage of biosynthesis technology, namely, significantly reducing the particle size of the adsorbent material through microbial metabolic processes. This feature not only effectively increases the surface area of ​​the binding membrane and improves adsorption capacity, but also embodies the principles of sustainable green chemistry.

[0026] 3. The combined membrane of the present invention has a high adsorption capacity for As, with the adsorption capacities of As(III) and As(V) being 55.0 and 131.2 μg·cm, respectively. -2 The elution efficiency in 0.5M sodium hydroxide solution reaches 98%, which is superior to several commonly used DGT-bound membranes for measuring inorganic arsenic, such as hydrated iron oxide-DGT and zirconium oxide-DGT. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a schematic flow chart of the preparation method of the biosynthetic titanium dioxide modified (Bio-TiO2-DGT) combined membrane of the present invention.

[0028] Figure 2 Bio-TiO2-DGT combined membrane was prepared by adding different concentrations of TiO(OH)2 solution.

[0029] Figure 3 is a scanning electron microscope image of the titanium dioxide modified bonded membrane obtained by biological synthesis and non-biological synthesis in a specific embodiment, wherein: Figure 3 a is a scanning electron microscope image of the Bio-TiO2-DGT combined membrane, Figure 3 b is a scanning electron microscopy image of the non-biologically synthesized titanium dioxide modified (TiO2-DGT) binding membrane.

[0030] Figure 4 ] is a particle size distribution diagram of the binding membrane in a specific embodiment, wherein, Figure 4 a is the particle size distribution diagram of Bio-TiO2-DGT combined membrane, Figure 4 b is the particle size distribution diagram of TiO2-DGT combined membrane.

[0031] Figure 5 2 are X-ray diffraction patterns (XRD) of the Bio-TiO2-DGT combined membrane and the TiO2-DGT combined membrane prepared in a specific embodiment.

[0032] Figure 6FTIR spectra of the Bio-TiO2-DGT combined membrane and the TiO2-DGT combined membrane prepared in a specific embodiment.

[0033] Figure 7 This is a diagram of the adsorption performance of the Bio-TiO2-DGT combined membrane at different adsorption times in a specific embodiment.

[0034] Figure 8 This is a diagram of the adsorption performance of the Bio-TiO2-DGT combined membrane at different initial As(III) / As(V) concentrations in a specific embodiment.

[0035] Figure 9 The As(III) / As(V) binding capacity of the Bio-TiO2-DGT combined membrane in a specific embodiment is compared with several other commonly used DGT combined membranes.

[0036] Figure 10 Graph showing the adsorption performance of As(III) / As(V) by the Bio-TiO2-DGT device at different pH values ​​in a specific embodiment.

[0037] Figure 11 Graph showing the adsorption performance of As(III) / As(V) by the Bio-TiO2-DGT device under different ionic strengths in a specific embodiment.

[0038] Figure 12 This is a specific implementation method for the application of Bio-TiO2-DGT and high-resolution two-dimensional imaging analysis of As at the soil-water interface. DETAILED DESCRIPTION

[0039] The present invention will be further described in detail below through specific examples. The following examples are only illustrative and not restrictive, and the scope of protection of the present invention cannot be limited thereto.

[0040] A nano-scale, ultra-uniform titanium dioxide (DGT)-bound membrane with high arsenic adsorption efficiency is described. Its composition consists of a biosynthesized titanium dioxide-modified membrane material (Bio-TiO2-DGT), a diffusion membrane, and a nitrocellulose membrane. Using TiO(OH)2 as the raw material, the strain XZ-1 biosynthesizes the membrane, achieving in-situ precipitation of TiO2.

[0041] The diffusion membrane preparation method is as follows: 170 mL of gel solution is prepared. Weigh 0.6 g of allyl-modified low-temperature active agarose (the public document is CN103752285A), dissolve it in 95 mL of hot water, and ultrasonically dissolve it until it is completely dissolved. Weigh 30 g of acrylamide and dissolve it in 75 mL of deionized water. Add the above-mentioned acrylamide solution to the cross-linker solution, mix it ultrasonically, and obtain a gel solution. Ultrasonic mix 10 mL of gel solution with 25 μL of 10% ammonium persulfate and 70 μL of N,N,N`,N`-tetramethylethylenediamine (TEMED). Pump it into two glass plates separated by a gasket of a certain thickness through a peristaltic pump, seal it, and cure it at 42°C for 1 hour to obtain a diffusion membrane.

[0042] The volume ratio of the gel solution: 10% ammonium persulfate: TEMED is 400:1:2.8.

[0043] The thickness of the diffusion membrane and the bonding membrane is set according to the requirements. The diffusion coefficients obtained by different thickness diffusion membranes are different. The thickness of the diffusion membrane and the bonding membrane used in the present invention are both 0.04 cm, and the corresponding diffusion coefficients of As(III) and As(V) are 0.546×10 -6 cm 2 ·s -1 and 0.711×10 -6 cm 2 ·s -1 .

[0044] The Bio-TiO2-DGT combined membrane preparation method is not limited to the type of diffusion membrane, that is, it is applicable to various types of diffusion membranes, but the obtained diffusion coefficient needs to be recalculated.

[0045] The preparation method of the Bio-TiO2-DGT combined membrane is as follows:

[0046] S1. Biosynthesis step: 10 mL of bacterial suspension and 3 diffusion membranes were mixed with 500 mL of 0.5 mol / L TiO(OH)2 solution in a constant temperature shaker at 30°C for 3 h.

[0047] S2. Chemical precipitation: After mixing, rinse with deionized water 1-2 times to wash away the bacteria, then immerse in 100 mL of 0.05 mol / L 2-(N-morpholino)ethanesulfonic acid (MES) buffer, which has been pre-adjusted to pH 6.7 with approximately 4 mL of 1 mol / L NaOH solution. A white precipitate appears after soaking for a certain period of time.

[0048] S3, water change and storage: After about 40 minutes of gentle shaking to allow the gel to fully develop, the gel was removed from the buffer and soaked in MQ water for 24 hours, during which time the water was changed 5-6 times, and then -1Soak in NaNO3 and store in a 4℃ refrigerator for later use.

[0049] Example 1

[0050] A method for preparing a nano-ultra-uniform titanium dioxide DGT-bound membrane for efficient As adsorption comprises the following steps:

[0051] Using titanic acid (TiO(OH)2) as the raw material, strain XZ-1 was added for biosynthesis. During this process, a pre-prepared diffusion membrane was immersed in it to ensure full contact with the reaction system. The biological action of the strain promoted the conversion of TiO(OH)2, achieving in-situ precipitation of TiO2, and thus preparing a Bio-TiO2-DGT combined membrane.

[0052] It can be used for two-dimensional high-resolution imaging analysis of arsenic in water, soil, and sediment. The elution solution is 0.5M sodium hydroxide, and the arsenic concentration in the bound membrane is calculated using Fick's first diffusion law.

[0053] like Figure 1 As shown, the preparation method of the Bio-TiO2-DGT combined membrane is as follows:

[0054] (1) Preparation of bacterial suspension: 100 μL of the activated strain XZ-1 was incubated in 50 mL of LB medium at 30°C on a shaking platform for 8 h. LB medium was prepared by dissolving 1 g of tryptophan, 0.5 g of yeast extract, and 1 g of NaCl in 100 mL of deionized water. The pH of the medium was adjusted to 7.0 with 1 mol / L NaOH.

[0055] (2) Preparation of TiO(OH)2 solution: 4.89 g of TiO(OH)2 powder was dissolved in 500 mL of deionized water and stirred at 60°C in a magnetic stirrer for 1 h.

[0056] (3) Preparation of Bio-TiO2-DGT combined membrane: 10 mL of bacterial suspension and 3 diffusion membranes were mixed with TiO(OH)2 solution and placed on a constant temperature shaker at 30°C for 3 h.

[0057] (4) The Bio-TiO2-DGT membrane was rinsed with deionized water 1-2 times to wash away the bacteria, and then immersed in 100 mL of 0.05 mol L -12-(N-morpholino)ethanesulfonic acid (MES, biochemical, BDH) buffer, which was pre-adjusted to pH 6.7 with approximately 4 mL of 1 mol / L NaOH solution. A white precipitate appeared after soaking for a certain period of time. After approximately 40 minutes of gentle shaking to allow the gel to fully develop, the gel was removed from the buffer and soaked in MQ water for 24 hours, during which time the water was changed 5-6 times, and then in 0.01 mol·L -1 Soak in NaNO3 and store in a 4℃ refrigerator for later use.

[0058] (5) Cut the Bio-TiO2-DGT combined membrane into discs and assemble them into a circular DGT device. The assembly steps are as follows: place the protective membrane, diffusion membrane and Bio-TiO2-DGT combined membrane on the base of the circular DGT device from top to bottom, and then buckle the DGT device shell and tighten it.

[0059] Example 2

[0060] In order to explore the advantages of the biosynthesis method in the embodiment of the present invention, this embodiment prepared a non-biosynthetic TiO2-DGT binding membrane, that is, the binding membrane was prepared by biosynthesis without adding strain XZ-1, and the remaining steps were the same as the Bio-TiO2-DGT binding membrane.

[0061] Example 3

[0062] Screening of the Optimal TiO(OH)2 Concentration for Preparation of Bio-TiO2-DGT Combined Membranes by In-situ Precipitation of Microbially Synthesized TiO2

[0063] In order to explore the optimal conditions for preparing Bio-TiO2-DGT combined membrane, 1.63g and 4.89g of TiO(OH)2 were added respectively, and Bio-TiO2-DGT combined membrane was prepared according to the steps of Example 1. The results are shown in Figure 2. Figure 2 As shown, Figure 2 Figures 2a and 2b are Bio-TiO2-DGT membranes prepared using 1.63g and 4.89g of TiO(OH)2, respectively. The Bio-TiO2-DGT membrane prepared using 4.89g of TiO(OH)2 exhibits a darker milky white surface, indicating a better precipitation effect.

[0064] Example 4

[0065] Analysis of Nano-Ultra-Uniform Titanium Dioxide-DGT Combined Membrane with High Efficiency in As Adsorption

[0066] In order to explore the microstructure and chemical properties of the Bio-TiO2-DGT and TiO2-DGT combined membranes, the present invention uses scanning electron microscopy (SEM), particle size distribution, X-ray diffraction (XRD) and infrared spectroscopy (FTIR) characterization methods to analyze the combined membranes obtained in Example 1 and Example 2.

[0067] See also Figure 3 , Figure 3 a is a scanning electron microscope image of the Bio-TiO2-DGT combined membrane, Figure 3 b is a scanning electron micrograph of a non-biosynthetic titanium dioxide-modified (TiO2-DGT) membrane. The biosynthetic Bio-TiO2-DGT membrane exhibits a more uniform surface, while the non-biosynthetic TiO2-DGT membrane exhibits surface agglomeration.

[0068] See also Figure 4 , Figure 4 a is the particle size distribution diagram of Bio-TiO2-DGT combined membrane, Figure 4 Figure b shows the particle size distribution of the TiO2-DGT membrane. The figure shows that the Bio-TiO2-DGT membrane has an average particle size of 66.4 nm, demonstrating a more uniform particle size distribution. In contrast, the non-biosynthetic TiO2-DGT membrane has an average particle size of 88.5 nm, which is larger and more uneven.

[0069] See also Figure 5 , Figure 5 These are the X-ray diffraction patterns (XRD) of the Bio-TiO2-DGT combined membrane and the TiO2-DGT combined membrane, in which characteristic peaks appeared at 25.281°, 48.049°, 53.890°, and 55.060°, indicating that the obtained materials meet the characteristics of titanium dioxide.

[0070] See also Figure 6 , Figure 6 The infrared spectra (FTIR) of Bio-TiO2-DGT combined membrane and TiO2-DGT combined membrane are shown in the figure. The wavelengths of the FTIR spectra are 3181.94, 1646.20, 1599.64, 1410.42, and 1039.36 cm -1 The absorption peaks at 1316.28, 1177.93 and 1114.30 are the characteristic peaks of C-OH. The Bio-TiO2-DGT combined membrane has an additional 1039.36 cm-1 absorption peak compared to the TiO2-DGT combined membrane. -1 The absorption peak at , which is the vibration peak of CO.

[0071] Example 5

[0072] Performance test of Bio-TiO2-DGT combined membrane

[0073] The concentration is 100 μg·L -1 As(III) and As(V) solutions were prepared with a total volume of 10 mL, a pH of 7.0 ± 0.5, and a background ion concentration of 0.01 mol·L -1 The specific operation is: the cut circular Bio-TiO2-DGT combined membrane is placed in 10mL of 0.01mol·L -1 100 μg·L of NaNO3 as the matrix -1 The As(III) and As(V) solutions were prepared in triplicate. The samples were shaken at 150 rpm at 25°C. After 0.5 min, 5 min, 15 min, 30 min, 1 h, 2 h, 4 h, 8 h, 12 h, and 24 h, 0.5 mL of the supernatant was taken and diluted 2-fold to 1 mL with deionized water. The As(III) and As(V) concentrations were detected by a 0.22 μm filter. The results are shown in the figure. Figure 7 As shown in the figure, the adsorption of As(III) and As(V) by the Bio-TiO2-DGT combined membrane reached adsorption equilibrium in about 4 hours, and the adsorption rate of As(V) was higher than that of As(III).

[0074] Example 6

[0075] Performance test of Bio-TiO2-DGT combined membrane

[0076] Prepare As(III) and As(V) solutions of different concentrations (0.1, 1, 10, 20, 40, 60, 80, 100 mg·L -1 ), the total volume of the solution was 10 mL, the pH was adjusted to 7.0 ± 0.5, and the background ion concentration was 0.01 mol·L -1 The specific operation is: the cut circular Bio-TiO2-DGT combined membrane is placed in 10mL of 0.01mol·L -1 The samples were shaken in a shaker at 25°C and 150 rpm for 6 hours, and the supernatant concentration was measured. The results were fitted using Langmuir and Freundlich adsorption isotherms, and the maximum adsorption capacity of the bound gel was calculated. Figure 8 As shown in Figure 2, the adsorption curves of As(III) and As(V) on the Bio-TiO2-DGT membrane were fitted by Langmuir, and the maximum adsorption capacities were 55.0 and 131.2 μg·cm, respectively. -2This indicates that the Bio-TiO2-DGT combined membrane has a higher adsorption capacity for As(V) than for As(III).

[0077] Example 7

[0078] Performance test of Bio-TiO2-DGT combined membrane

[0079] The concentration is 100 μg·L -1 As(III) and As(V) solutions were prepared by adjusting the pH values ​​to 3, 4, 5, 6, 7, and 8, respectively. The total volume of the solution was 2 L, and the background ion concentration was 0.01 mol·L -1 The specific operation is: 3 circular DGT devices with Bio-TiO2-DGT membranes were placed in 2L As(III) and As(V) solutions of different pH values, and a magnetic stirrer was used to keep the solution in constant motion for 6h. Figure 9 As shown, when the pH value is in the range of 5-7, C DGT / C solu The value fluctuates between 0.96-1.07, with little effect. However, when the acidity or alkalinity increases, that is, when the pH value is 4 and 8, C DGT / C solu The value varies between 0.87-0.94. This means that when the pH is within the range of 4-8, the overall C DGT / C solu The change of pH value is within the acceptable range, but the pH value has a greater impact under overly acidic or overly alkaline conditions.

[0080] Example 8

[0081] Performance test of Bio-TiO2-DGT combined membrane

[0082] Prepare NaNO3 with different ionic strengths (0.0001, 0.001, 0.005, 0.01, 0.1 mol·L -1 ) is 100 μg·L of matrix -1 The total volume of the As(III) and As(V) solutions was 2 L and the pH was adjusted to 7.0±0.5. The specific operation was as follows: 3 circular DGT devices with Bio-TiO2-DGT membrane were placed in 2 L of As(III) and As(V) solutions with different ionic strengths, and a magnetic stirrer was used to keep the solution in constant motion for 6 hours. The results are shown in Figure 2. Figure 10 As shown, the ionic strength is 0.0001-0.1 mol·L -1 When the range changes, C DGT / C soluThe value varies between 0.9 and 1.1, and the error is within an acceptable range, indicating that the accuracy of Bio-TiO2-DGT is not affected by the increase of ionic strength.

[0083] Example 9

[0084] Comparison of As(III) / As(V) Binding Capacity of Bio-TiO2-DGT Combined Membranes

[0085] Several commonly reported types of DGT-bound membranes, including Metsob, Ferrihydrite, Zr-oxide, and ZrO-Chelex, were selected for comparison with Bio-TiO2 and Chem-TiO2. Figure 11 As shown in the results, the combined membranes of Bio-TiO2 and Chem-TiO2 have better adsorption capacities for As(III) than Metsob, Ferrihydrite, Zr-oxide, and ZrO-Chelex, and better adsorption capacities for As(V) than Metsob, Ferrihydrite, and ZrO-Chelex. Among them, the combined membrane of Bio-TiO2 has the best capacity for As(III) / As(V).

[0086] Example 10

[0087] High-resolution measurement of arsenic in soil using Bio-TiO2-DGT combined membrane

[0088] High-resolution two-dimensional measurements of arsenic were performed using Bio-TiO2-DGT to investigate the effect of soil flooding on the distribution of As in soil profiles. Flat DGT (15cm*2cm) was used in this experiment to extract the As content in the soil profile. One kilogram of air-dried soil was placed in a (9 cm × 15 cm, diameter × height) barrel and 1 liter of deionized water was added to ensure that the flooding layer was approximately 2 cm and the soil layer was approximately 12 cm. The flat DGT was placed in the soil and the average As flux was measured after 20 days of flooding. The bound gel that was flooded for 10 days and deployed for 24 hours was used to analyze the two-dimensional distribution of soil As flux by LA-ICP-MS under a 110μm spot. The results are shown in the figure. Figure 12 As shown, Bio-TiO2-DGT can meet the monitoring needs of finer high-resolution (micrometer-level) two-dimensional capture of As at the environmental interface, providing a new and feasible binding gel material for DGT technology in the field of high-resolution two-dimensional analysis.

[0089] Although the embodiments of the present invention are disclosed for illustrative purposes, those skilled in the art will understand that various substitutions, changes and modifications are possible without departing from the spirit and scope of the present invention and the appended claims. Therefore, the scope of the present invention is not limited to the contents disclosed in the embodiments.

Claims

1. A nano-ultra-uniform titanium dioxide DGT combined membrane with high efficiency in adsorbing As, characterized in that: In order to utilize strain XZ-1 to synthesize TiO2 and precipitate it in situ on the diffusion membrane, a Bio-TiO2-DGT combined membrane with uniform particle size was obtained.

2. The nano-ultra-uniform titanium dioxide DGT combined membrane for efficient As adsorption according to claim 1 is characterized in that: The strain XZ-1, the strain name is: XZ-1, the classification name is: Pantoea sp., the preservation number is: CGMCCNo.32330, the preservation date is: October 24, 2024, the preservation unit is: General Microbiology Center of China Microbiological Culture Collection Administration, and the preservation address is: Institute of Microbiology, Chinese Academy of Sciences, No. 3, No. 1 Beichen West Road, Chaoyang District, Beijing.

3. A method for preparing a nano-ultra-uniform titanium dioxide DGT-bound membrane for efficient As adsorption as claimed in claim 2, characterized in that: The steps include: Using titanic acid as raw material, the strain XZ-1 is used for the biosynthesis process. During this process, the pre-prepared diffusion membrane is immersed to fully contact the reaction system. The biological action of the strain XZ-1 promotes the conversion of TiO(OH)2, realizes the in-situ precipitation of TiO2, and then prepares the Bio-TiO2-DGT combined membrane.

4. The method for preparing the nano-ultra-uniform titanium dioxide DGT combined membrane for efficient As adsorption according to claim 3 is characterized in that: The preparation method of the diffusion membrane comprises the following steps: ultrasonically mixing a gel solution, ammonium persulfate and N,N,N',N'-tetramethylethylenediamine, pumping the mixture into two glass plates separated by a 0.04-0.08 cm thick gasket through a peristaltic pump, and curing the mixture under sealing to obtain a diffusion membrane.

5. The method for preparing the nano-ultra-uniform titanium dioxide DGT combined membrane for efficient As adsorption according to claim 4 is characterized in that: The volume ratio of the gel solution, ammonium persulfate and N,N,N',N'-tetramethylethylenediamine is 400:1-5:2-10.

6. The method for preparing the nano-ultra-uniform titanium dioxide DGT combined membrane for efficient As adsorption according to claim 5 is characterized in that: The gel solution is obtained by mixing acrylamide and allyl-modified low-temperature active agarose.

7. The method for preparing a nano-ultra-uniform titanium dioxide DGT-bound membrane for efficient As adsorption according to claim 6, characterized in that: The method for preparing the nano-ultra-uniform titanium dioxide DGT combined membrane for efficient As adsorption specifically comprises the following steps: S1, biosynthesis: the concentration is 0.5×10 9 CFU / mL bacterial suspension and 1-5 diffusion membranes were mixed with 0.5-1 mol / L TiO(OH)2 solution in a constant temperature shaker at 20-30℃ for 2-5h; S2, chemical precipitation: after mixing, rinse with deionized water 1-2 times to wash away the bacteria, and then immerse in 100mL 0.05mol / L 2-(N-morpholine)ethanesulfonic acid buffer, the buffer solution is pre-adjusted to pH 6.7 with 1mol / L NaOH solution, and soak until white precipitate appears; S3, water change, storage: After 20-60 minutes of gentle shaking to allow the gel to fully develop, the gel was removed from the buffer and soaked in MQ water for 24 hours, during which the water was changed 5-6 times, and then heated to 0.01 mol·L -1 Soak in NaNO3 to obtain the Bio-TiO2-DGT combined membrane, and store it in a 4℃ refrigerator for later use.

8. Use of the nano-ultra-uniform titanium dioxide DGT combined membrane with high efficiency in As adsorption as claimed in claim 2 in two-dimensional high-resolution imaging analysis of As.

9. A method for preparing a DGT-bound membrane suitable for two-dimensional high-resolution imaging analysis of As as described in claim 8, characterized in that: The steps include: (1) Preparation of bacterial suspension: 100 μL of the activated strain XZ-1 was incubated in 50 mL LB medium at 30° C. for 8 hours on a shaking table; wherein the LB medium was prepared as follows: 1 g tryptophan, 0.5 g yeast extract, and 1 g NaCl were dissolved in 100 mL deionized water, and the pH of the medium was adjusted to 7.0 with 1 mol / L NaOH; (2) Preparation of TiO(OH)2 solution: 4.89 g of TiO(OH)2 powder was dissolved in 500 mL of deionized water and stirred at 60 °C in a magnetic stirrer for 1 h. (3) Preparation of Bio-TiO2-DGT combined membrane: 10 mL of bacterial suspension and diffusion membrane were mixed with TiO(OH)2 solution and placed on a constant temperature shaker at 30 °C for 3 h. After mixing, the membrane was rinsed with deionized water 1-2 times to wash away the bacteria, and then immersed in 100 mL of 0.05 mol L -1 2-(N-morpholino)ethanesulfonic acid buffer, which was pre-adjusted to pH 6.7 with 4 mL of 1 mol / L NaOH solution, was soaked until a white precipitate appeared. After 40-60 minutes of gentle shaking to allow the gel to fully develop, the gel was removed from the buffer and soaked in deionized water for 24 hours, during which the water was changed 5-6 times, and then in 0.01 mol·L -1 Soak in NaNO3 and store in a 4℃ refrigerator for later use.

10. The method for preparing a DGT-bound membrane suitable for two-dimensional high-resolution imaging analysis of As according to claim 9, characterized in that: The XZ-1 bacterial suspension was cultured in LB medium at 30°C in a constant temperature shaker, and the bacterial cells were incubated on a constant temperature shaker at 180 rpm to the late exponential phase for 8 hours to obtain the above bacterial suspension.

Citation Information

Patent Citations

  • Absorbent material for water body purification and biological carbon brick

    CN103752285A

Cited By

  • Detection device for clinical detection or self-detection of respiratory pathogens and preparation method of detection device

    CN121299115A

  • A detection device for clinical detection or self-detection of respiratory pathogens and a preparation method thereof

    CN121299115B